the Promoting Reproductive Health Preventive Behaviours in Married Women Workers - Demirci, Hulya; KARANİSOĞLU, Hacer (British Journal of Healthcare and Medical Research, 2023)
This study was conducted in order to determine the knowledge levels, behaviours and attitudes of married women workers about reproductive health preventive behaviours. This study was carried out semi-experimental research. Population of the research was consisted was consisted of 160 women who work in factory A. 25 volunteer women who were chosen by convenience sampling method were included to “Reproductive Health Education Programme”. The research data were collected by using a “Women Information Form”, “Women's health knowledge test” and “The Scale for Determining the Reproductive Health Preventive Attitudes of Married Women” was used. It was determined that, women workers’ knowledge levels, behaviours and attitudes about reproductive health preventive behaviours were inadequate and there weren’t any comprehensive education programmes in A factory. When the efficacy of the health education programme for women was evaluated, it was found that the programme was successful in general; the difference before and three months after education for Women Health Knowledge Test, Total Scale Point and subscale points of “Preventing Genital Infections”, “Viziting Doctor In Reproductive Health Related Issues”, “Preventing Reproductive System and Breast Cancers”, “General Health Behaviours for Preventing Reproductive Health” were statistically significant. It has been determined that there is a significant difference between the reproductive health of women who Pre-training and Post-training and that training positively affects the reproductive health practices of women. It has been determined that the training provided to women is an effective initiative in increasing the reproductive health practices of women.